Interrelating Motivation to Learn Chinese with the Needs of Chinese Language Professionals in Globalization 5.0 Era - Sheyra Silvia Siregar; Rina Supriatnaningsih; Anggraeni (PT FORMOSA CENDEKIA GLOBAL, 2024)
Competition in the Industrial 5.0 era requires mastery of a second language, one of which is Mandarin. Several studies have shown an increase in Mandarin as a curriculum in some schools in the United States (Dillon, 2010). Similarly, in Indonesia, both national and international schools have piloted Mandarin (Yudono, 2012). The factors that influence the motivation of learning Mandarin according to Sadiman are internal factors and external factors. The purpose of this study was to describe the motivation of final year students of the Chinese Language Education Sutdi Program at UNNES towards the job prospects of foreign companies from China in Central Java. The participants who became the object of this study were Mandarin Language Education Study Program students in the 6th semester as many as 30 students who were expected to be ready to enter the industrial world as a form of answer to the need for Mandarin language experts in various industrial fields in Central Java. One of the phenomena found by researchers is the decline in student motivation as seen from the results of the final semester exam which is at an average of 65. The instrument used in this study is a questionnaire based on the independent variable and the dependent variable and then distributed to students as the main data. The results of the questionnaire were measured using a Likert scale.